The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.6002/ect.2012.0063
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of New-Onset Diabetes After Transplant: Single-Centre Experience

Abstract: Objectives: We sought to study the prevalence, risk factors, and long-term prognosis of posttransplant diabetes mellitus. Materials and Methods:We studied all patients with end-stage renal disease without diabetic nephropathy who received a kidney transplant and were followed-up at our center since 1983 (n=218; age, 44.3 ± 13.1 y). Patients with new-onset diabetes after transplant were compared to kidney transplant recipients without risk factors for diabetes mellitus. Patients with new-onset diabetes after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
(70 reference statements)
4
17
1
Order By: Relevance
“…Results from other studies indicating a comparable incidence of NODAT among KTRs with or without HCV infection may be less reliable for excluding various confounders . The present study suggests a significant role of HCV infection in NODAT development, which is in accordance with results from other studies . A meta‐analysis provided retrospective evidence of a 3.97‐fold increased risk of NODAT in HCV‐infected KTRs .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Results from other studies indicating a comparable incidence of NODAT among KTRs with or without HCV infection may be less reliable for excluding various confounders . The present study suggests a significant role of HCV infection in NODAT development, which is in accordance with results from other studies . A meta‐analysis provided retrospective evidence of a 3.97‐fold increased risk of NODAT in HCV‐infected KTRs .…”
Section: Discussionsupporting
confidence: 84%
“…23,24,26 The present study suggests a significant role of HCV infection in NODAT development, which is in accordance with results from other studies. 2,4,20 A meta-analysis provided retrospective evidence of a 3.97-fold increased risk of NODAT in HCVinfected KTRs. 1 Successful anti-HCV therapy was reported to greatly ameliorate glucose dysregulation, 37 which supports the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of HCV‐associated NODAT is higher when traditional risk factors such as high BMI, metabolic syndrome, a positive family history for diabetes mellitus, older age and ethnicity (Hispanic or African‐American) are present . In HCV‐infected recipients, NODAT manifests usually in the first months after transplantation when higher doses of immunosuppressants are administered .…”
Section: Natural History and Clinical Course Of Chronic Hepatitis Cmentioning
confidence: 99%
“…Clinical studies indicate that tacrolimus (TAC) is associated with a higher risk for IGT and NODAT than is cyclosporine. It is not defined whether the effect of CNI on glucose metabolism is dosage-dependent (4). A large retrospective registry showed that new onset diabetes after kidney transplantation is a significant, independent predictor of total mortality and loss of graft function.…”
Section: Introductionmentioning
confidence: 99%